Interaction of the histone (H3-H4)2 tetramer of the nucleosome with positively supercoiled DNA minicircles: Potential flipping of the protein from a left- to a right-handed superhelical form. - Hamiche, A (1996)
We have studied the ability of the histone (H3-H4)2 tetramer, the central part of the nucleosome of eukaryotic chromatin, to form particles on DNA minicircles of negative and positive superhelicities, and the effect of relaxing these particles with topoisomerase I. The results show that even modest positive torsional stress from the DNA, and in particular that generated by DNA thermal fluctuations, can trigger a major, reversible change in the conformation of the particle. Neither a large excess of naked DNA, nor a crosslink between the two H3s prevented the transition from one form to the other. This suggested that during the transition, the histones neither dissociated from the DNA nor were even significantly reshuffled. Moreover, the particles reconstituted on negatively and positively supercoiled minicircles look similar under electron microscopy. These data agree best with a transition involving a switch of the wrapped DNA from a left- to a right-handed superhelix. It is further proposed, based on the left-handed overall superhelical conformation of the tetramer within the octamer [Arents, G., Burlingame, R. W., Wang, B. C., Love, W. E. & Moudrianakis, E. N. (1991) Proc. Natl.Acad. Sci. USA 88, 10148-10152] that this change in DNA topology is mediated by a similar change in the topology of the tetramer itself, which may occur through a rotation (or a localized deformation) of the two H3-H4 dimers about their H3-H3 interface. Potential implications of this model for nucleosome dynamics in vivo are discussed.